Why is it important to use regional lenses when we look into civil conflicts in the Mena? - Hamati, Samer (2019)
Investigating different political and social variables in the Middle East and North Africa (MENA) is receiving more attention between social scientists, particularly in the peace and conflict institutes. This is due to the uniqueness of the region and to the violent conflicts it has witnessed for the last decades. These conflicts become intrastate but transitional, hence transfer into internationalized civil conflicts, and have large externalities exceeding the region borders. These conflicts show the high connectedness between the MENA countries, and recently the Arab Spring affirms the ‘contagion effect’ of upheavals in the region. Following multidisciplinary approach, this research note is a try to explain how much important it is to study the MENA conflicts from a regional perspective and to present the factors proving the contagion effects there. We hope that when reading this note, the reader will sufficiently understand the regional aspects of the MENA conflicts.